Adamantane-Modified Graphene Oxide for Cyanate Ester Resin Composites with Improved Properties - Zhicong Miao; Juntao Shi; Tianjiao Liu; Peng Li; Zhiqiang Su; Gang Wei (Applied Sciences, 2019)
The conjugation of graphene and polymers has attracted great attention for the fabrication of functional hybrid nanomaterials. Here, we demonstrate the modification of graphene oxide (GO) with adamantane (AMT) through the diimide-activated amidation reaction. The modification of GO with AMT improves the dispersion and decreases the interfacial polarization of GO, causing a lower dielectric constant for the fabricated GO/AMT hybrid materials. The structures of GO/AMT were studied by Fourier transform infrared spectroscopy and Raman spectroscopy. Furthermore, the mechanical properties, thermal stability, and dielectric constant of GO/AMT composites were measured at a low cured temperature using various techniques, such as differential scanning calorimetry, thermogravimetric analysis, and dynamic mechanical thermal analysis. It was found that the synthesized GO/AMT materials with different contents were blended into cyanate ester (CE) resins, resulting in a lower cure temperature, smaller dielectric constant, higher thermal stability, and stronger water resistance. It is expected that this novel GO/AMT-CE material will have potential applications for replacing traditional thermosetting resins.